Man against Microbes: No Victor, No Vanquished - Deboye, Kolawole (Obafemi Awolowo University Press, 2013)
The topic - "MAN AGAINST MICROBES: NO VICTOR, NO VANQUISHEO" is suggestive of a battle between man and microbes, which cannot be said to have been won or lost on either side. Man is the highest of God's creation, to whom He gave dominion overall other creatures, while microbes are organisms that are too small to be seen with the naked eye, but are present in large numbers everywhere. Both man and microbes have therefore existed side by side-through the ages. With man not being able to see the microbes until in the nineteenth century, but all the while seeing and experiencing the effects of their activities, especially the harmful effects which helped to draw attention to them.